Effects of exciton-polariton on Mach-Zehnder interference devices - Arith, Faiz; Mustafa, Ahmad Nizamuddin; Idris, Idzdihar; Abdul Latiff, Anas; Toshio, Katsuyama (Maxwell Scientific Organization, 2014)
A new optoelectronic device based on excitonpolariton was studied. In particular a Mach-Zehnder interference device fabricated by using a GaAs quantum well was studied. We simulated the output characteristics of Mach-Zehnder interference device by using a Finite Difference Time Domain (FDTD) method. Then we compared them with the experimental results measured in a low-temperature. After that we obtained the numerical values of electro-optic effect coefficients. Those were as large as 105×10-11 m/V for 4.5 K, while 74×10-11 m/V for 77 K. Therefore this estimation is considerably large, showing 57 (4 K) and 41 (77 K) times larger than conventional KDP crystal. This effect is probably caused by the excitonpolariton effect. Furthermore, we performed a photocurrent experiment to understand the transmitted light phase change characteristics, causing such large electro-optics effect at a comparatively higher temperature. Temperature dependence of photocurrent showed that the absorption edge and exciton peak remained constant up to 77 K, and then shifted to lower energy as the temperature increased. This probably explains how the large electro-optic effect can be obtained at a comparatively high temperature, i.e., 77 K.